(untitled) (Nigerian Journal of Pharmaceutical Research, 2020)
Background: Nauclea diderrichii is used in West and Central Africa countries for its insecticidal and antiparasitic properties. There is, however, no documentation on its activity against parasitic nematodes. Objectives: This study investigated N. diderrichii leaf extracts and fractions for anthelmintic activity against adult Haemonchus placei, an abomasal parasitic worm that infect cattle. Materials and Method: Pulverized dried leaves of N. diderrichii was defatted using n-hexane, followed by successive extraction using chloroform and acetone. The extracts were evaluated for anthelmintic activity by incubating ten (10) adult H. placei in a range of concentrations (1 ̶ 20 mg/mL) for 3h and then counting the number of confirmed dead worms. The most active extract was subjected to chromatographic fractionation, and the thin layer chromatographic (TLC) profile of the fractions was documented. The dried fractions were then evaluated for anthelmintic activity and anthelmintic data were fitted to a non-linear regression equation (Log [extract or fraction] vs. response; variable slope) to produce best-fit sigmoidal curves and LC50 values computed. Results: Anthelmintic assay shows that acetone extract is worm-active with a best-fit LC50 of 16.24 mg/mL, while the chloroform extract was inactive. Fractionation of the acetone extract yielded three fractions (FA, FB and FC) and TLC profile revealed the various secondary metabolites in the fractions. Of the fractions, only fraction B was active against H. placei with LC50 of 12.24 mg/mL. Conclusion: Acetone extract of N. diderrichii leaf possessed anthelmintic activity against adult H. placei, and could be useful as anthelmintic phytomedicine to deworm cattle.